Modified Coronally Advanced Flap Technique for Managing Orthodontic Related Gingival Recession - Fabia Yustiaputri; Eka F Augustina; I Gusti A Aditya Putra (CV. Publikasi Indonesia, 2026)
Background: Gingival recession is one of the most common mucogingival deformities requiring surgical correction. Various mucogingival therapies are available as treatment options for gingival recession, such as connective tissue graft, coronally positioned flap, and acellular dermal matrix application. The acellular dermal matrix (ADM) contains undamaged collagen and elastin matrices and can be used as a substitute for a connective tissue graft (CTG) during the root coverage procedure. This case report studies the effects of ADM graft (SureDerm®) combined with coronally advanced flap (CAF) on root coverage and aesthetics for the treatment of multiple gingival recessions associated with orthodontic treatment in patients with a thin gingival phenotype. A 25-year-old male patient presented to the Periodontics Specialist Clinic at the Dental Hospital, Universitas Airlangga, with the chief complaint of dental hypersensitivity and aesthetic concerns in the maxillary central incisors. The patient had undergone orthodontic treatment for two years and had worn a mandibular lingual retainer for two years before the mucogingival therapy. A modified envelope papilla preservation technique with the additional use of acellular dermal matrix (SureDerm®) was performed to improve gingival thickness and reduce recession length. The three-month follow-up showed an increase in gingival thickness and a decrease in recession length. The success of this treatment depends on the surgical technique and procedure used, and it is measured by the absence of further complaints and the correction of gingival recession. The coronally advanced flap technique with the additional use of acellular dermal matrix (SureDerm®) is effective for managing orthodontic-related gingival recession.